Sports technology provides an objective assessment of the Paralympic swimming classification system - Evershed, J.-A.; Frazer, S.; Mellifont, R.; Burkett, B. (Sports Technology, 2012)
The Paralympic Games are the highest form of competition for an athlete with a disability and the fundamental distinction between the Olympic and Paralympic Games is the Paralympic classification system. Recently the International Paralympic Committee mandated the development of an evidence-based classification system for each sport. To create an objective Paralympic classification system this study firstly evaluated the current classification musculoskeletal protocols with swimming specific equipment. To mitigate against the numerous physical variations in people with a disability, 32 elite able-bodied swimmers were assessed. Using a custom-built bilateral swim bench ergometer and a 3D Motion Monitor (120Hz) system, upper-limb kinematic and performance measures (hand force) were collected and compared to the musculoskeletal protocols. There were inconsistent and generally weak correlations between the current classification system range of motion scores, and the actual 3D kinematic range of motion, with similar weak correlations to hand force. Although not evident in the relatively static musculoskeletal protocols, important swimming specific asymmetry differences were identified in shoulder abduction/adduction along with external rotation, via the sports technology assessment. These findings highlight firstly the deficiencies in the current classification system, followed by the advantages of implementing sport-specific technology to objectively address this international issue.